Long-term anatomical and functional outcomes of surgical treatment of retinal complications in children and adolescents with Stickler syndrome between 2004 and 2021 - Burdová, Marie Česká; Štěpánková, Jana; Pourová, Radka Kremlíková; Mahelková, Gabriela; Hložánek, Martin; Kožner, Pavel; Dotřelová, Dagmar (Graefe's archive for clinical and experimental ophthalmology, 2023)
BACKGROUND: Stickler syndrome (STL) is an inherited progressive connective tissue collagen disorder. STL is the most common hereditary cause of retinal complications, retinal tears, and the development of retinal detachment (RD) in childhood. The aim of the study was to evaluate the long-term anatomical and functional results of surgical treatment of retinal complications in children and adolescents affected by STL. METHODS: A retrospective, single-center study was performed a cohort of children with STL who underwent retinal surgery between 2004 and 2021. RESULTS: The study group consisted of nine children; the mean age at the time of the retinal tear with/without retinal detachment was 7.2 (2-10) years, and the mean follow-up period was 9.6 (5-16) years. Pathogenic variants COL2A1 (5 children) and COL11A1 (3 children) were confirmed in our cohort. In total, we operated on 13 eyes, 11 eyes with complicated RD and two eyes with multiple retinal defects, but without RD. At the end of the follow-up period, an attached retina was achieved 77% (10 eyes) with or without silicone oil tamponade: cryopexy alone was successful in one eye (10%), scleral buckling (EB) in five eyes (50%), and vitrectomy with silicone oil tamponade combined with EB in four eyes (40%). The mean number of surgeries was 2.3 per eye. The resulting best corrected visual acuity ranged from 0.03 to 0.1 in one eye, from 0.16 to 0.4 in two eyes, and from 0.5 to 1.0 in 7 eyes. CONCLUSION: Repair of retinal tears with/without retinal detachment in patients with Stickler syndrome often requires multiple surgeries with combinations of cryopexy, scleral buckling, and/or vitrectomy with silicone oil tamponade. Treatment of the ocular complications arising from STL requires long-term comprehensive care.
Keywords: Vitrectomy; Scleral Buckling; Retinal complication; retrospektivní studie; nemoci pojiva; Humans; Retinal Perforations; bukláž skléry; Retinal surgery; Connective Tissue Diseases; retina; Eye Diseases, Hereditary; Hearing Loss, Sensorineural; Retinal detachment; silikonové oleje; odchlípení sítnice; perforace sítnice; Adolescent; COL2A1; výsledek terapie; COL11A1; Treatment Outcome; Stickler syndrome; Retinal Detachment; Silicone Oils; dědičné nemoci očí; percepční nedoslýchavost; vitrektomie; lidé; artritida; mladiství; dítě; Arthritis; Child; Retrospective Studies; Retina